The Development of Digital Content Set for Promoting KMUTT Library on an Online Platform - Thamwipat, Kuntida; Princhankol, Pornpapatsorn; Putwattana, Pongpatcharin; Ponya, Aunchaliyon; Saisemapakavat, Wipanee (Siam Communication Review, 2025)
This research aimed to 1) develop the digital content set for promoting KMUTT Library on an online platform, 2) evaluate the quality of the developed digital content, 3) assess the perception of the sample group toward the developed digital content, and 4) evaluate the satisfaction of the sample group with the digital content set for promoting the KMUTT Library on an online platform. The research tools included 1) the developed digital content set for promoting the KMUTT Library on an online platform, 2) a quality assessment form of the digital content set developed, 3) a perception evaluation form for the sample group, and 4) a satisfaction evaluation form for the sample group. The sample group consisted of followers of the Instagram account kmuttlibrary, selected through accidental random sampling. The participants included 50 followers who had previously viewed the developed digital content set and were willing to respond to the questionnaire. The data were gathered in the first semester of the 2024 academic year. The development results included the design and creation of 6 sets of infographic posters and 4 short video clips. Subsequently, these materials were submitted to experts for quality evaluation. The assessment results indicated that the content quality was rated at a very good level (X= 4.80, S.D. = 0.46) while the media presentation quality also received a very good rating ( X= 4.61, S.D. = 0.49). Additionally, the sample group's perception was rated at the highest level ( X= 4.75, S.D. = 0.55), and their satisfaction achieved the highest rating as well ( X= 4.85, S.D. = 0.36). Therefore, the developed digital content set for promoting the KMUTT Library on an online platform was suitable for practical implementation.